2021
DOI: 10.1097/gox.0000000000003699
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Nerve Transfers in Acute Flaccid Myelitis Patients: A Case Series

Abstract: Background: Acute flaccid myelitis (AFM) is characterized by flaccid paralysis following prodromal symptoms. Complete recovery is rare, and patients typically have residual extremity weakness. This study aimed to describe the technique and outcomes of lower extremity nerve transfers for children with AFM. Methods: A retrospective review of eight children who developed AFM in 2016 and had lower extremity nerve transfers was performed. Principles of nerve transfer were applied to develop novel nerve transfer pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
(74 reference statements)
0
9
0
1
Order By: Relevance
“…After removal of duplicates and initial screening, 500 were reviewed and assessed for eligibility. After application of inclusion and exclusion criteria, 99 articles were included in this study (55 case reports/series, 1,4–7,9–57 33 retrospective cohort studies, 2,3,58–88 seven cross-sectional studies, 89–95 and four case-control studies 96–99 ) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of duplicates and initial screening, 500 were reviewed and assessed for eligibility. After application of inclusion and exclusion criteria, 99 articles were included in this study (55 case reports/series, 1,4–7,9–57 33 retrospective cohort studies, 2,3,58–88 seven cross-sectional studies, 89–95 and four case-control studies 96–99 ) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…19 Moore and colleagues described eight patients with proximal lower extremity weakness treated with a variety of techniques, particularly sciatic fascicle transfer to superior or inferior gluteal nerve or vastus medialis transfers, six of whom had improvement in lower extremity Medical Research Council muscle strength grade. 44 Lubelski et al reported bilateral sciatic fascicle–to-femoral transfers in four patients with persistent proximal lower extremity weakness, but did not provide postoperative outcomes. 41 Overall, 44 of the 61 patients analyzed (72.1%) had improvement in strength in at least one muscle group.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in cases of injury from trauma or THA that could result in injury to the SGN and also to the sciatic nerve, the tibial division is rarely affected, which supports the likelihood that it will be available as a donor in cases that could ultimately benefit from nerve transfer (Simske et al, 2019; Wilson et al, 2018). Recent study by Moore et al (2021) presented that eight children who had flaccid paralysis due to acute flaccid myelitis underwent nerve transfer and all patients reported improvement Medical Research Council (MRC) grades.…”
Section: Discussionmentioning
confidence: 99%
“…Ischial tuberosity = IT and greater trochanter = greater trochanter of the femur nerve transfer (Simske et al, 2019;Wilson et al, 2018). Recent study by Moore et al (2021) presented that eight children who had flaccid paralysis due to acute flaccid myelitis underwent nerve transfer and all patients reported improvement Medical Research Council (MRC) grades.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve transfers either end-to-end transfers or side-to-end nerve transfers are another potential option with limited data ( 47 , 48 ). One study showed patients improved from a manual muscle testing score of 0–3 ( 48 ).…”
Section: Managementmentioning
confidence: 99%